An Oxa[5]helicene-Based Racemic Semiconducting Glassy Film for Photothermally Stable Perovskite Solar Cells - Niansheng Xu (iScience, 2019)
Summary: Attaining the durability of high-efficiency perovskite solar cells (PSCs) operated under concomitant light and thermal stresses is still a serious concern before large-scale application. It is crucial to maintain the phase stability of the organic hole-transporting layer for thermostable PSCs across a range of temperatures sampled during device operation. To address this issue, we propose a racemic semiconducting glassy film with remarkable morphological stability, exemplified here by a low-molecular symmetry oxa[5]helicene-centered organic semiconductor (O5H-OMeDPA). The helical configuration of O5H-OMeDPA confers the trait of multiple-dimension charge transfer to the solid, resulting in high hole mobility of 6.7 × 10−4 cm2 V−1 s−1 of a solution-processed glassy film. O5H-OMeDPA is combined with a triple-cation dual-halide lead perovskite to fabricate PSCs with power conversion efficiencies of 21.03%, outperforming the control cells with spiro-OMeTAD (20.44%). Moreover, the cells using O5H-OMeDPA exhibit good long-term stability during full-sunlight soaking at 60°C. : Chemistry; Materials Science; Surface Science; Energy Materials Subject Areas: Chemistry, Materials Science, Surface Science, Energy Materials